2021
DOI: 10.22460/project.v4i2.p202-207
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Cooperative Learning Type Teams Game Tournament (Tgt) Method to Improve Students Motivation in Learning English

Abstract: The objective of this research is to describe the implementation of teams game tournament in learning English at SMP Pasundan 1 Cimahi. The research using descriptive qualitative method, and took 33 samples from seventh grade students. The writer collected data by interviewing and spreading questionnaires asked the students motivation which have 10 items adopted from Muhlisin, (2018). Percentage and descriptive explanations are applied in data processing. Based on this study, the writer found that; 1. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…In other words, the treatment implemented in the experimental class is more effective in promoting students' grammatical knowledge in an online learning setting. This finding echoed the previous studies on the effectiveness of teams-gametournament in promoting students' English knowledge and abilities (Astria & Maisaroh, 2021;Gani, 2019;Karman & Indriani, 2021;Pransiska, 2021) particularly English grammar as the study conducted by Munawir et al (2018) and Hasanah (2021), adding new insights that teaching grammar using the given strategy through Whatsapp group is effective in advancing senior high school students' grammar understanding. The results from this study will contribute to the existing literature on the advantages of TGT as a type of cooperative learning model to teach grammar where it enables students to have more interactions during online learning, which in turn increases their understanding of the materials that are proven by the enhancement of their grammar test achievement.…”
Section: Table 5 the Progress Analysis Of Students' Grammar Scoressupporting
confidence: 81%
See 1 more Smart Citation
“…In other words, the treatment implemented in the experimental class is more effective in promoting students' grammatical knowledge in an online learning setting. This finding echoed the previous studies on the effectiveness of teams-gametournament in promoting students' English knowledge and abilities (Astria & Maisaroh, 2021;Gani, 2019;Karman & Indriani, 2021;Pransiska, 2021) particularly English grammar as the study conducted by Munawir et al (2018) and Hasanah (2021), adding new insights that teaching grammar using the given strategy through Whatsapp group is effective in advancing senior high school students' grammar understanding. The results from this study will contribute to the existing literature on the advantages of TGT as a type of cooperative learning model to teach grammar where it enables students to have more interactions during online learning, which in turn increases their understanding of the materials that are proven by the enhancement of their grammar test achievement.…”
Section: Table 5 the Progress Analysis Of Students' Grammar Scoressupporting
confidence: 81%
“…It was also revealed that when this learning model is used in the teachinglearning process, it improved students' speaking skills and created a favorable atmosphere (Meiliawati, 2021). Moreover, related to learners' motivation, studies revealed that TGT could promote students' motivation to learn English (Pransiska, 2021), particularly in learning English grammar in higher educational context (Hasanah, 2021).…”
Section: Introductionmentioning
confidence: 99%